2015
DOI: 10.1152/jn.00247.2015
|View full text |Cite
|
Sign up to set email alerts
|

The optimal neural strategy for a stable motor task requires a compromise between level of muscle cocontraction and synaptic gain of afferent feedback

Abstract: Dideriksen JL, Negro F, Farina D. The optimal neural strategy for a stable motor task requires a compromise between level of muscle cocontraction and synaptic gain of afferent feedback. J Neurophysiol 114: 1895-1911, 2015. First published July 22, 2015 doi:10.1152/jn.00247.2015.-Increasing joint stiffness by cocontraction of antagonist muscles and compensatory reflexes are neural strategies to minimize the impact of unexpected perturbations on movement. Combining these strategies, however, may compromise stea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 150 publications
(182 reference statements)
2
26
0
Order By: Relevance
“…A higher level of coactivation limits the potential torque at the joint and may contribute to an age-related difference in strength of agonist muscles (Macaluso et al 2002). Increased coactivation can also increase joint stiffness and thus reduce the impact of perturbations during joint movement (Gribble et al 2003; Dideriksen et al 2015) and this is consistent with old adults increasing the activation of antagonist muscles during dynamic contractions to stabilize the joint during movement.…”
Section: Discussionsupporting
confidence: 68%
“…A higher level of coactivation limits the potential torque at the joint and may contribute to an age-related difference in strength of agonist muscles (Macaluso et al 2002). Increased coactivation can also increase joint stiffness and thus reduce the impact of perturbations during joint movement (Gribble et al 2003; Dideriksen et al 2015) and this is consistent with old adults increasing the activation of antagonist muscles during dynamic contractions to stabilize the joint during movement.…”
Section: Discussionsupporting
confidence: 68%
“…Altering the sensitivity of muscle spindle to muscle length and its rate of change in simulations was not sufficient to reshape the primary afferent activity to reflect muscle activity features. Altogether, these results suggest that to solve the neuromechanical problem, the CNS controls limb dynamics through dynamics-dependent co-activation of muscles and non-linear modulation of monosynaptic primary afferent feedback (Roberts et al, 2008) (Perez et al, 2007) (Dideriksen et al, 2015).…”
Section: Discussionmentioning
confidence: 89%
“…This is due in part to the complexity of the sensorimotor control loop. The prevailing theory of motor control is that the CNS embeds complex mechanical limb dynamics in order to shape control signals and incorporate sensory feedback (Kluzik et al, 2008;Kurtzer et al, 2008;Wagner and Smith, 2008;Dideriksen et al, 2015). This embedding at the supra-spinal level is often referred to as internal models (Kawato et al, 1987), which can be observed, for example, as dynamical units in the primary motor cortex (Churchland et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The reciprocal changes between Ia presynaptic inhibition and antagonist coactivation may reflect a strategy that consists of decreasing the contribution of the inputs from the muscle spindle afferents and increasing the reliance on coactivation to control the active stiffness of the ankle. This would be mechanically relevant because high reflex gain involves an inherent instability when maintaining a steady contraction, in particular, in the presence of antagonist coactivation (7). This interpretation is supported further by the observation of greater coactivation of agonist and antagonist in deafferented than in healthy subjects, suggesting a strategy based on controlling muscle activity with inputs from descending pathways when proprioceptive inputs are altered (27).…”
Section: Group Ia Afferent Input Onto Soleus Spinal Motor Neurons Durmentioning
confidence: 90%